(untitled) (International Journal of Engineering and Computer Science, 2016)
Identification of the soil is the key to avoid the losses in the quantity of the agricultural product and yield. The studies of the soil mean the studies of outwardly recognizable patterns seen on the soil. Soil grouping is extremely basic for feasible agribusiness. It is exceptionally hard monitor manually. It requires tremendous amount of work, and additionally require the inordinate processing time. Henceforth, image processing is utilized for the identification of soil. Soil recognition includes the steps like image acquisition, image pre-processing, feature extraction and classification. This project describes a Support Vector Machine based classification of soil samples